Carroll’s CSR pyramid model revisited: The contingent role of responsible leadership in insurance product innovation performance - Ghansah, Kyeame; Jagannathan, Uday Kumar; Mustapha, Rabiu Latif (The Economics and Finance Letters, 2026)
This study examines the relationship between Corporate Social Responsibility (CSR) and product innovation performance, focusing on the dimensions of responsible leadership, including ethical, transformational, and sustainability-oriented leadership as contingent factors. Using Partial Least Squares Structural Equation Modeling (PLS-SEM) with data from 370 employees across 49 insurance companies in Ghana, the findings reveal that economic CSR significantly impacts product innovation performance (β = 0.129, p = 0.038) of firms. While ethical CSR, legal CSR, and philanthropic CSR showed no direct effect relationships, there was evidence of indirect influences through responsible leadership. Moderation analysis indicates that ethical leadership strengthens the effect of economic CSR (β = 0.430, p = 0.001) as well as the negative effect of philanthropic CSR (β = -0.272, p = 0.006) on product innovation performance. Sustainability-oriented leadership also enhanced the relationships between philanthropic CSR (β = 0.312, p < 0.001), economic CSR (β = -0.355, p < 0.001), and product innovation performance. Additionally, transformational leadership was found to have a positive moderating effect on ethical CSR (β = 0.384, p = 0.015) and philanthropic CSR (β = 0.372, p < 0.001), and a negative moderating effect on legal CSR (β = -0.539, p = 0.002). Grounded in stakeholder and upper echelons theories, this study shows that insurers should integrate economic CSR with ethical and sustainability-oriented leadership to maximize product innovation. Firms in the finance sector, particularly insurers, should be intentional about their CSR strategies and incorporate the appropriate leadership techniques to achieve product innovation performance.